Negative pressure wound therapy in the treatment of surgical site infection in cardiac surgery - Mayra de Castro Oliveira; Alessandra Yuri Takehana de Andrade; Ruth Natalia Teresa Turrini; Vanessa de Brito Poveda
ABSTRACT Objectives: to describe the relationship between epidemiological and clinical characteristics of postoperative cardiac surgery patients undergoing negative pressure wound therapy for the treatment of surgical site infection. Methods: an observational, cross-sectional analytical study including a convenience sample consisting of medical records of patients undergoing sternal cardiac surgery with surgical site infection diagnosed in medical records treated by negative pressure wound therapy. Results: medical records of 117 patients, mainly submitted to myocardial revascularization surgery and with deep incisional surgical site infection (88; 75.2%). Negative pressure wound therapy was used on mean for 16 (±9.5) days/patient; 1.7% had complications associated with therapy and 53.8% had discomfort, especially pain (93.6%). The duration of therapy was related to the severity of SSI (p=0.010) and the number of exchanges performed (p=0.045). Conclusions: negative pressure wound therapy has few complications, but with discomfort to patients.